Meningkatkan Mutu Layanan Kesehatan Puskesmas melalui Penyediaan Air, Sanitasi, dan Kebersihan yang Berkelanjutan - Karolus Ngambut; Inriany Takesan (Universitas Mathla'ul Anwar Banten, 2021)
IMPROVING THE QUALITY OF HEALTH SERVICES AT PUSKESMAS THROUGH THE PROVISION OF SUSTAINAABLE WATER, SANITATION AND HYGIENE. The quality of Puskesmas health services as an effort to accelerate the achievement of UHC is hampered if basic water sanitation, sanitation and hygiene of health facilities are not yet available. The environmental health condition assessment was carried out at 11 Puskesmas in Kupang City and 7 Puskesmas in Kupang Regency, based on the Water and Sanitation for Health Facility Improvement Tool (WASH-FIT) developed by the World Health Organization. The results showed that the dimensions of water and environmental cleanliness in the red category were <67%. The dimensions of sanitation and medical waste management are yellow category, (67% -75%). The dimensions of hand hygiene and energy use and environment are green (> 75%). The water, sanitation and hygiene conditions of the community health centers in Kupang City are better than those of the health centers in Kupang District. Obstacles to the achievement of environmental health indicators include the competence of technical personnel for IPAL management, environmental health efforts at the health centers have not become a priority part of improving the quality of health services at the puskesmas, and environmental health efforts at puskesmas have not been well planned. It is recommended that the environmental health conditions of the puskesmas be considered, training for operators of medical waste treatment plants at puskemas needs to be carried out, funds for environmental health efforts are planned in the puskesmas budgeting.